Raw materials information network for Africa : a new agenda for development - Abdullahi, Ado K.; Ajoku, Kemjika B.; Raw Materials Research and Development (Abuja, Nigeria : Raw Materials Research and Development Council, 1998)
This book provides information on the resources of Africa, and equally highlights the crisis facing the economic development of the continent, as well as the various global initiatives designed to ensure Africa's economic survival in the 21st century.
Includes bibliographical references (p. 269).
rua 19/10/16
Loans
Keywords: Information technology; Raw materials research/development; Raw materials; Raw materials- information services; Africa